Pengaruh Sumber Daya manusia, Kesiapan Modal, Pemanfaatan E-Commerce Terhadap Daya Saing Usaha Mikro Kecil dan Menengah - Wulandari, Sinta (Expensive: Jurnal Akuntansi dan Keuangan, 2024)
This study aims to determine the effect of human resources, capital readiness and e-commerce utilization on the competitiveness of micro, small and medium enterprises (MSMEs) in Metro City. The type of research used in this research is quantitative with a descriptive approach. Data analysis was carried out by testing instruments, classical assumptions and testing hypotheses. The results of the study show that Human Resources have a positive and significant influence on the competitiveness of Micro, Small and Medium Enterprises (MSMEs) in Metro City. Capital readiness has a positive and significant influence on the competitiveness of Micro, Small and Medium Enterprises (MSMEs) in Metro City. E-Commerce has a positive and significant influence on purchasing decisions for Micro, Small and Medium Enterprises (MSMEs) in Metro City. Human Resources, capital readiness and E-Commerce have a positive and significant influence on the Competitiveness of Micro, Small and Medium Enterprises (MSMEs) in Metro City